Homozygous variegate porphyria presenting with developmental and language delay in childhood. (18th September 2013) - Pinder, V. A. E.; Holden, S. T.; Deshpande, C.; Siddiqui, A.; Mellerio, J. E.; Wraige, E.; Powell, A. M.
Summary Variegate porphyria is an autosomal dominant disorder that usually presents with photosensitivity and acute neurological crises in adulthood. It is caused by heterozygous mutations in the protoporphyrinogen oxidase gene (PPOX). A rarer variant, homozygous variegate porphyria (HVP), presents in childhood with recurrent skin blisters and scarring. More variable features of HVP are short stature, brachydactyly, nystagmus, epilepsy, developmental delay and mental retardation. We describe a child who presented with nystagmus, developmental delay and ataxia, combined with a photosensitive eruption. Analysis of porphyrins in plasma, urine and stool supported a clinical diagnosis of HVP. DNA from the patient showed that he is compound heterozygous for two novel missense mutations in the PPOX coding region: c.169G>C (p.Gly57Arg) and c.1259C>G (Pro420Arg). Interestingly, cranial magnetic resonance imaging showed an absence of myelin, a feature not previously reported in HVP, which expands the differential diagnosis of childhood hypomyelinating leucoencephalopathies.